Dopant-free, hole-transporting polymers containing benzotriazole acceptor unit for perovskite solar cells. (April 2022) - Cao, Jiabing; Wang, Lijun; You, Guofeng; Li, Lihua; Yao, Lu; Zhou, Zhonggao; Yang, E.; Cai, Wanzhu; Ling, Qidan; Zhen, Hongyu
Abstract: Dopant-free, electron donor (D)–acceptor (A) type, polymeric hole-transporting materials (HTMs) possess excellent film formability and hole transport properties, which ensure high efficiency, stability, and reproducibility to the PVSCs. Compared with benzothiadiazole (BT), benzotriazole (BTA) was less incorporated into polymeric HTMs. Herein, two indacenodithieno[3, 2-b]thiophene (IDTT)-BTA copolymers BT-T and BT-TT containing different π-bridge of thiophene and thienothiophene, are synthesized and studied. BT-T bearing thiophene π-bridge presents decent coplanarity, higher hole mobility, and better interface morphology than its sister polymer BT-TT. The PVSC with dopant-free BT-T displayed a peak power conversion efficiency (PCE) of 17.1% and remained above 85% of its initial PCE for more than 30 days at ambient conditions. In view of the rare report on the BTA-based polymeric HTMs, this work will cast lights on further exploration of high-efficiency D-A polymeric HTMs. Graphical abstract: Two indacenodithieno[3, 2-b]thiophene-benzotriazole copolymers BT-T and BT-TT containing π-bridge of thiophene and thienothiophene, respectively, are developed as dopant-free hole-transporting materials. Image 1 Highlights: Two polymers containing benzotriazole are developed as hole-transporting materials. π-bridge of thiophene endows BT-T higher coplanarity and hole mobility. BT-T shows superior hole transport properties to BT-TT with thienothiophene π-bridge. The perovskite solar cells based on dopant-free BT-T display an efficiency of 17.1%.